374 CORRELATION BETWEEN RENAL INSUFFICIENCY AND WHITE MATTER HYPERDENSITY IN ELDERLY PATIENTS: A RANDOMIZED RETROSPECTIVE CHART REVIEW. Issue 1 (1st January 2007) - Gnanasekaran, G.; Gravenstein, S.; Gowrishankar, S.
Abstract : Background: Renovascular disease and cerebrovascular disease are among the top 10 causes of death in elderly people. Measures of GFR correlate with kidney disease, whereas white matter hyperdensities (WMHs) correlate with cerebrovascular disease. Little is published describing the occurrence and severity of these together. We hypothesize that both renovascular and cerebrovascular conditions share a common origin and the presence of one predicts the presence of the other, both in terms of occurrence and severity. Methods: We conducted a randomized retrospective chart review of inpatients aged 60 to 70 years in a tertiary care teaching hospital between January 1, 2004, and May 31, 2005, who had brain imaging and serum creatinine measurement done during their hospitalization. A sample size was set for an alpha level of 0.05 to detect r > .5 with 80% power. Subjects' medical records were reviewed for concurrent imaging data, serum creatinine, age, gender, and race. MDRD formula was used to calculate GFR. The main outcome measures were the occurrence and severity of WMHs in patients with renal insufficiency. A Pearson correlation was used to estimate the relationship between the two variables. Chi-square analysis was done to determine statistical significance. Results: Of 1, 000 eligible patients, 200 were randomly selected. A total of 161 subjects were evaluable, after excluding 39 subjects with ESRD or a previous history of strokes. Of these, we found no GFR impairment (> 90 mL/min) in 70 subjects, mild impairment (60-89 mL/min) in 36 subjects, moderate impairment (30-59 mL/min) in 47 subjects, and severe impairment (15-29 mL/min) in 8 subjects. In subjects with normal GFR, 96% (67/70) had mild WMH and 4% (3/70) had moderate WMH. No severe WMH was found in this group. In subjects with mild renal insufficiency, WMH was mild in 81% (29/36), moderate in 17% (6/36), and severe in 3% (1/36). In subjects with moderate kidney disease, 21% (10/47), 66% (31/47), and 13% (6/47) had mild, moderate, and severe WMH, respectively. With severe kidney disease, none of the subjects had mild WMH, whereas 37.5% (3/8) had moderate and 62.5% (5/8) had severe WMH. A Pearson correlation yielded a value of 0.76 with a p value of .01. WMH and renal insufficiency were similarly correlated when analyzed by gender and race. Conclusion: The severity of white matter disease and severity of renal insufficiency correlate. GFR may have functional correlates with cognition. Further research will help define the importance of this relationship in CNS disease prevention.